Stress and Its Consequences—Biological Strain - Stevenson, David K.; Gotlib, Ian H.; Buthmann, Jessica L.; Marié, Ivana; Aghaeepour, Nima; Gaudilliere, Brice; Angst, Martin S.; Darmstadt, Gary L.; Druzin, Maurice L.; Wong, Ronald J.; Shaw, Gary M.; Katz, Michael (American Journal of Perinatology, 2022)
Understanding the role of stress in pregnancy and its consequences is important, particularly given documented associations between maternal stress and preterm birth and other pathological outcomes. Physical and psychological stressors can elicit the same biological responses, known as biological strain. Chronic stressors, like poverty and racism (race-based discriminatory treatment), may create a legacy or trajectory of biological strain that no amount of coping can relieve in the absence of larger-scale socio-behavioral or societal changes. An integrative approach that takes into consideration simultaneously social and biological determinants of stress may provide the best insights into the risk of preterm birth. The most successful computational approaches and the most predictive machine-learning models are likely to be those that combine information about the stressors and the biological strain (for example, as measured by different omics) experienced during pregnancy.
Keywords: pregnancy; preterm birth; omics; machine learning